Blue Notes: Using Songwriting to Improve Student Mental Health and Wellbeing. A Pilot Randomised Controlled Trial - Gee, Kate A.; Hawes, Vanessa; Cox, Nicholas Alexander (Frontiers in Psychology, 2019)
Higher Education is a period of transition. Students try out identities, develop skills, and explore their shifting sense-of-self. Recent evidence suggests an increase in mental distress in this population, pressurising in-house support schemes. Therapeutic songwriting is a music therapy technique, which can reduce mental distress and improve social engagement in a range of clinical populations; yet it is also an accessible art form, possibly an ideal vehicle for supporting students in distress. This paper examines whether participation in a weekly songwriting program could make a suitable RCT to support wellbeing within the HE environment. We used a methodologically rigorous pre-registered parallel wait-list pilot RCT design. Trial registration: ISRCTN11180007. Participants self-identifying as stressed, anxious, or depressed, or with a pre-existing mental health condition, were randomly allocated to the experimental group (five weeks, songwriting) (n=6) or to the wait-list control group (five weeks, no intervention) (n=6). Measures were taken at baseline and at the start (Time 1) and end (Time 2) of the intervention. Measures included: depression and anxiety scales, social identification, loneliness, and friendship. Change scores were calculated and a Mann Whitney U revealed that depression levels in songwriters (Mdn = -1.0) differed significantly from wait-list controls (Mdn = 8.5) at T2, U = 5.00, z = -2.085, p < .041, r = 2.66. Songwriters’ levels of social connection (Mdn = 2.50) also differed significantly from wait-list controls (Mdn = 3.00) at T2 U =3.00, z = -2.441, p < .015, r = 0.524. There were no other significant differences between control and intervention groups. A therapeutic songwriting intervention may have individual and group level benefits for a student population, alongside possible institutional benefits in student retention. Effects may be seen within depression and social connection metrics, and future RCTs should consider expanding measures for self-efficacy, social isolation, and wellbeing. This type of program illustrates a space for cost-effective, group, face to face additions institutional mental health support provision as part of a package of support for students.